Audiovisual Services Sector: Can the Philippines Follow "Bollywood?" - Angelina M. Lantin; Gloria O. Pasadilla (Philippine Institute for Development Studies (PIDS), 2005)
The paper is an industry study of the audiovisual services sector, specially the film and television industry in the Philippines. It discusses the importance of the sector in the economy and employment, its strengths and weaknesses, regulations that affect it, and the competitive forces that influence the key participants. The paper also discusses the technological developments such as digital technology that are changing the mode of delivery and consumption of audiovisual services. The paper notes its export potential because of the growing Filipino population abroad that continues to crave for local movies and programs, and considers ways how the Philippines can replicate the relative success of India, China, and Korea in breaking through the global market.
Keywords: 330; film industry; trade in services; General Agreement on Trade in Services (GATS); audiovisual services; Dienstleistungshandel; Mediensektor; Filmwirtschaft; GATS; Philippinen